Notes per a l'estudi del procés de codificació i estandardització del català al segle XX - Segarra, Mila (Caplletra. Revista Internacional de Filologia, 1999)
A critical overview of the state of studies in the history of codification and standardization, a central issue in the contemporary history of Catalan. The author divides her study into three periods (1913-1939, 1939-1983, 1983-1999), which are thematically separated codification and dissemination of grammar, model of literary language, linguistic models in the audio-visual media, public debates on language), and indicates their outcomes and shortcomings.